Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145361
|View full text |Cite
|
Sign up to set email alerts
|

Tie strength in question & answer on social network sites

Abstract: Asking friends, colleagues, or other trusted people to help answer a question or find information is a familiar and tried-and-true concept. Widespread use of online social networks has made social information seeking easier, and has provided researchers with opportunities to better observe this process. In this paper, we relate question answering to tie strength, a metric drawn from sociology describing how close a friendship is.We present a study evaluating the role of tie strength in question answers. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 22 publications
0
61
0
Order By: Relevance
“…Panovich et al [34] studied the role of tie strength in answering questions. Through user studies they found that answers from users with whom the questioner shares stronger ties provide slightly more information than those from people with weaker ties.…”
Section: Related Workmentioning
confidence: 99%
“…Panovich et al [34] studied the role of tie strength in answering questions. Through user studies they found that answers from users with whom the questioner shares stronger ties provide slightly more information than those from people with weaker ties.…”
Section: Related Workmentioning
confidence: 99%
“…This line of investigation has also explored social network analysis to benefit CQA service. For example, Katrina et al [12] presented a study relating tie strength to answer quality for questions asked on social network sites and they found that stronger ties actually provided better answers for some measures of answer quality.…”
Section: Related Workmentioning
confidence: 99%
“…Those seeking information and support online, particularly through SNSs, are likely to be able to access a much higher number of sources and answers to questions than they would through face-to-face contact [18] due to having access to a larger pool of contacts [19]. Furthermore, the sources of information people access online may be considered more reliable, accurate or trustworthy by information seekers [20].…”
Section: Introductionmentioning
confidence: 99%